GAMBARAN TINGKAT DEPRESI WARGA BINAAN LEMBAGA PEMASYARAKATAN KELAS II A KENDAL - Yulia Ardiyanti; Rokatun Rokatun; Fatikhah Fatikhah; Alvi Ratna Yuliana; Adriyanti Wing Karyika Sari5 (Jurnal Profesi Keperawatan, 2026)
Depression is one of the most common mental health problems experienced by inmates in correctional institutions due to psychological stress, limited freedom, and lack of social support. This condition can affect inmates’ psychological well-being and hinder the rehabilitation process if not properly identified and managed. This study aimed to determine the level of depression among inmates at Class II A Correctional Institution in Kendal. A quantitative descriptive research design was employed in this study. The population consisted of all inmates at the Class II A Correctional Institution in Kendal, with a total of 73 respondents selected using a total sampling technique. Data were collected using a standardized depression questionnaire. Data analysis was conducted using descriptive statistics by calculating frequency distribution and percentage to describe the depression levels of the respondents. The results showed that the majority of inmates experienced severe depression, with 51 respondents (69.9%) classified as having severe depression and 22 respondents (30.1%) classified as having mild depression. These findings indicate that the prevalence of severe depression among inmates at Class II A Correctional Institution in Kendal is high and represents a significant mental health concern. The high level of severe depression suggests that inmates face considerable psychological burdens that may affect their psychosocial functioning and participation in rehabilitation programs. In conclusion, most inmates at Class II A Correctional Institution in Kendal experience severe depression, highlighting the need for enhanced mental health services, including regular depression screening, psychological counseling, and programs that promote psychological well-being among inmates.